Critical Analysis of Healthcare Sustainability in Environmental Impact, Resource Management, and Ethical Considerations - Alsharari, Albanadria Shwayhit Luwayfi; Atwi, Sara Salamh; Abuaeaaq, Zafaran Khaled Salem; Alanazi, Fahad Saad Kurdi; Alanazi, Faisal Khalid Mohammed; Aldoshan, Mohsen Yahya Mohsen; Alyami, Sara Blaal S; Alazmi, Mona Ayed; Al-Anzi, Hani Mukhlef Khalaf; Alabas, Salem Bader; Alsharif, Abdulrahman Hussain Rabia Allah (Journal of Ecohumanism, 2024)
For people, healthcare systems are crucial; the flip side is that these same systems are highly unsustainable in terms of the waste they produce, their carbon footprint, and the resources they consume. Health care sustainability involves consideration of the environmental impact, resource use, as well as ethical issues. This paper evaluates these three perspectives: as a driver of environmental degeneration through climate change, its contribution towards sustainability, and equity concerning environmental justice. Information presented and case descriptions and discussion focus on obstacles and best practices to incorporate sustainability into healthcare organizations.